Photonic Microbricks: Fabrication of Photonic Microbricks via Crack Engineering of Colloidal Crystals (Adv. Funct. Mater. 26/2020). (25th June 2020) - Phillips, Katherine R.; Zhang, Cathy T.; Yang, Ting; Kay, Theresa; Gao, Chao; Brandt, Soeren; Liu, Lei; Yang, Haizhao; Li, Yaning; Aizenberg, Joanna; Li, Ling
Abstract : In article number 1908242, Ling Li and co‐workers provide a mechanistic understanding of crack formations during the evaporation‐induced self‐assembly of colloidal crystals, which allows for rational controlling of the location and orientation of cracks for fabricating photonic microstructures with controlled geometries and sizes.